Study on Optimization of Extraction Process of Saponins from Bulbus Lilii and Their Antidepressant Effects - Zhang, Xiao-Yi; Han, Xiao-Lin; Qian, Zhi-Bin (Asian Journal of Chemistry, 2014)
Lilium brownii is used for dreaminess, absent-mindedness. The extraction of polysaccharide and saponin constituents in Bulbus Lilii have been extensively studied, but relatively little attention has been paid to the process. The objective of the study is to investigate the extraction process of saponins from Bulbus Lilii and their antidepressant effects in mice. Orthogonal experiment was used to optimize the concentration and amount of the extraction solvent, as well as the extraction time of Bulbus Lilii saponins, meanwhile, immobility time of mice in the tail suspension and forced swimming tests and antagonism of reserpine-induced hypothermia were observed. As results optimal process for the extraction of saponins from Bulbus Lilii was 1 time heat reflux extraction with 70 % ethanol for 3 h; compared with the control group, each Bulbus Lilii saponin experimental group could significantly shorten the immobility time of mice in the tail suspension and forced swimming tests and could effectively antagonize reserpine-induced hypothermia in mice as well. It is concluded that Bulbus Lilii saponins have antidepressant effects.